The effectiveness of a team intervention to enhance team regulation in hybrid teams: a randomized controlled trial - Althammer, Sarah Elena; Wöhrmann, Anne Marit; Michel, Alexandra (European journal of work and organizational psychology, 2025)
This article evaluates the effectiveness of a team intervention for hybrid work teams. In the intervention, hybrid work teams engaged in team-regulatory strategies with the aim to improve hybrid team collaboration. In a cluster-randomized controlled trial, data from 478 individuals across 56 hybrid work teams working with flexible work designs (FWD, flexibility in where, when and how to work) were used to examine the intervention effectiveness on FWD-specific social support, psychological safety, and psychosocial management as an indicator of team collaboration. Teams were assigned to an intervention group that received the intervention immediately (n = 229) or to a waitlist control group (n = 249). Participants received questionnaires before and after the intervention and at a 9-week follow-up. The results of multilevel analyses showed that the intervention improved FWD-specific social support and psychological safety with small to medium effect sizes and psychosocial management with a large effect size. Team regulation mediated effects. Medium effects on team regulation and psychosocial management as well as a small effect on psychological safety persisted over 9 weeks.
Gesehen am 21.01.2026